Pengembangan Kemandirian Anak Usia 5-6 Tahun Di Tk Dharmawanita Tunas Harapan - Silranti, Malia; Yaswinda, Yaswinda (Jurnal Caksana : Pendidikan Anak Usia Dini, 2019)
Abstract: This study was aimed at describing development of the independence of children aged 5-6 year in  TK Dharmawanita Tunas Harapan kindergarten in South. The research method is used  a qualitative descriptive. The data  were  gained  through  conducting  interviews,  observation  and  documentation.  The  data  were  then  analyzed using interactive model of data analysis from Miles and Huberman. The data was analyzed by using triangulation  technique through collection data, reduction,  display, and verification. The result of the study generally indicate that the development of independence in the Dharmawanita Tunas Harapan kindergarten in South Coastal district has been well implemente. But in planning it is not clearly described the development of children’s independence. Learning methods that are used by teachers in the development of independence are methods of habituation, conversation, question and Answer, playing, and giving assingment.